Gun Laws and Sudden Death : Did the Australian Firearms Legislation of 1996 Make a Difference? - Baker, Jeanine (The British journal of criminology, 2007)
Mass murders in Dunblane, United Kingdom, and Port Arthur, Australia, provoked rapid responses from the governments of both countries. Major changes to Australian laws resulted in a controversial buy-back of longarms and tighter legislation. The Australian situation enables evaluation of the effect of a national buy-back, accompanied by tightened legislation in a country with relatively secure borders. AutoRegressive Integrated Moving Average (ARIMA) was used to predict future values of the time series for homicide, suicide and accidental death before and after the 1996 National Firearms Agreement (NFA). When compared with observed values, firearm suicide was the only parameter the NFA may have influenced, although societal factors could also have influenced observed changes. The findings have profound implications for future firearm legislation policy direction